Educational restructuring : international perspectives on traveling policies - Lindblad, Sverker, 1946-; Popkewitz, Thomas S. (International perspectives on educational policy, research, and practice., 2004)
A volume in International Perspectives on Educational Policy, Research and Practice. Series Editor: Kathryn M. Borman, University of South Florida.